Upaya Peningkatan Ketahanan Pangan Dengan Menggunakan Pupuk Organik Cair Di Desa Astanalanggar - Pribadi, Riky; Dewi, Rani; Farhan Syafiq, Herry (Universitas Majalengka, 2025)
Food security is one of the main pillars of national development as mandated by Law Number 18 of 2012 concerning Food. Astanalanggar Village as one of the villages with potential in the agricultural sector faces various challenges in increasing the productivity and quality of agricultural products. Problems related to food security. Lack of public awareness of the dangers of continuous use of chemical fertilizers. Continuous use of chemical fertilizers will have a negative impact on the environment. This community service activity aims to: 1. Increase community knowledge and skills in producing liquid organic fertilizer independently; 2. Encourage the application of liquid organic fertilizers on community agricultural land. 3. Increase the productivity and quality of agricultural products as part of strengthening village food security and 3. Realize a more environmentally friendly and sustainable agricultural system. The work programs implemented from August 7, 2023, to August 11, 2023, included: 1. Counseling on the dangers of chemical fertilizer use for future soil fertility. The result of this work program was the creation of a liquid organic fertilizer (POC) product to improve soil nutrients damaged by excessive use of chemical fertilizers in Astanalanggar village. 2. Counseling on the utilization of vacant land by creating vertical planting. The potential that can be leveraged from this program is the utilization of unproductive vacant land into productive land by using vertical planting.